Investigating Students’ Speaking Skills through Traditional Story-Based Digital Storytelling into Genre-Based Approach (GBA) - Azzahra Henda Puspitasari , Putri; Lestari Damayanti, Ika; Nurlaelawati , Iyen (Jurnal Pedagogy, 2024)
Digital storytelling has been widely used in the English learning process as a way to improve language skills, especially speaking skills, but the influence of digital storytelling on students' speaking skills in traditional stories that integrated into the Genre-Based Approach (GBA). This study aims to investigate the students’ speaking skills development by using traditional story-based digital storytelling into GBA. A qualitative case study was used in this research involving 22 students at a private junior high school using observations, interviews, and digital storytelling projects. Thematic analysis was chosen to analyze the data which was categorized to obtain themes in answering the development of speaking skills through the integration of traditional story-based digital storytelling into Genre-Based Approach. The findings indicate that students who engage in all stages of the Genre-Based Approach (GBA) through traditional story-based digital storytelling demonstrate improvements in English vocabulary, word pronunciation, accuracy, and speaking fluency during various GBA activities. Self-confidence also influences and supports them to tell traditional stories digitally in a spoken way. Apart from that, at Joint Construction of the Text (JCoT) stage, students helped by discussions and teamwork in creating digital storytelling which encouraged them to be able to create digital storytelling independently. Future implementation of digital storytelling at various levels of education is recommended to develop students' English language skills.